UPAYA GURU PENDIDIKAN AGAMA ISLAMDALAM MENINGKATKAN SPIRITUAL QUOSTIENT SISWADI SMP IBNU SINA MOJOKERTO: Efforts Of Islamic Religious Education Teachers In Improving Students' Spiritual Quotient At Ibnu Sina Middle School, Mojokerto - Sholikhin, Anwar; Abdul Halim (Piwulang: Jurnal Pendidikan Agama Islam, 2025)
Teachers are human figures whose presence and role are expected in education, as resources that occupy positions and play important roles in life. Spiritual Intelligence or Spiritual Quostient is an awareness that not only recognizes existing values ​​but also creatively discovers new values. This research uses a qualitative case study approach. Data collection through observation, interviews, and documentation. Data collection, data presentation, and drawing conclusions are the data analysis techniques used in this study. The results of this study can be summarized as follows: (1) Activities that increase students' Spiritual Quostient include congregational Dhuhur prayer, congregational Dhuha prayer, Quranic recitation, and reciting the Asmaul Husana (the Beautiful Names of Allah). (2) Efforts made by teachers to increase students' Spiritual Quostient through good planning in congregational Dhuhur prayer, starting from preparation, implementation, and the results of student changes. Teachers feel an increase in students' spiritual intelligence, seen from the students' increased enthusiasm in participating in this congregational Dhuhur prayer activity. The existence of Dhuhur prayer activities can increase students' spiritual intelligence with the following indicators: (a) Students are orderly and disciplined in congregational prayer (b) Self-awareness to worship increases (c) Improves good relations between teachers and students (d) A sense of responsibility arises in students.